Emerging infections in a world out of balance - Perera, Jennifer (My University, 2000)
The world has become much more vulnerable to the widespread and even global spread of both new and old infectious diseases. Conditions conducive to the emergence and re-emergence of infectious diseases involve complex interplay between environmental, microbial and human behavioral and socio-economic factors. An emerging infection has been defined as a disease that comes to our attention because it involves a newly identified organism e.g. Human Immunodeficiency Virus (HIV), or a known organism that newly started to cause disease (e.g. microsporidia) or an organism whose transmission or virulence has increased, e.g. multidrug resistant tuberculosis (MDR TB), vancomycin resistant enterococci (VRE), methicillin resistant S.aureus (MRSA). Shortly before the first cases of unexplained immunodeficiency among homosexual males were being recognized in the USA, the world health assembly announced that small pox has been eradicated throughout the world1 . Moreover at that time there was wide spread optimism that many infectious diseases were under control, preventable or curable. The HIV epidemic, emergence antimicrobial resistance and the emergence of other infectious diseases all proved that this optimism was ill founded. Clearly, infectious diseases are among the most important issues facing medicine at the end of this century, just as they were at the end of the last century. The last 20 years have witnessed a rapid change in the spectrum of infectious diseases in both developing and developed countries and this currently threatens the health of populations throughout the world. What I would like to address today is ‘How changes in human behavior and the resulting new ecology have affected the spread of infectious diseases’. The human factors responsible for ecological changes include population growth, poverty, human migration caused by war, famine, geopolitical conditions, modern technology, rapid and creasing international travel and changing personal behavior